NEW MATHEMATICS TUTORIAL FOR TECHNOLOGY STUDENTS - N. N. GAZIZOVA; G. A. NIKONOVA; N. V. NIKONOVA (Высшее образование в России)
In the modern learning environment the classroom time is being substantially reduced and the volume of the studied material is being increased. University teachers have to make adjustments in the typical lessons and also in the traditional examination system. The consolidation of units and sections of studied discipline leads to the fact that small topics and sections are left without proper attention. To improve the quality of math education for technology students a special tutorial kit was created. This tutorial contains the lecture course, practical tasks for classroom lessons and tasks for homework. The kit allows each student to choose his (her) trajectory for learning and thereby to acquire the first skills of self-reliant work. The test control is being used in order to control the students’ learning outcomes. The usage of test technologies in educational process allows to increase the quality of learning, performance, objectivity and accuracy of assessment results of the learning process.